Strategi Suplementasi Protein Ransum Sapi Potong Berbasis Jerami dan Dedak Padi - B.W H.E Prasetiyono; . Suryahadi; T Toharmat; R Syarief (Faculty of Animal Science, Bogor Agricultural University, 2007)
ice straw and bran are low in protein. This study examined protein supplement (SPN) composed of CASREA (cassava-urea complex) and SOYXYL (protected-protein soybean meal) in rice straw and bran based ration offered to beef cattle. Experiment 1: Casrea1 (no extruded 32% urea and 58% cassava), Casrea2 (extruded 22% urea and 68% cassava), Casrea3 (extruded 27% urea and 63% cassava), and Casrea4 (extruded 32% urea and 58% cassava) were incubated in ruminal fluid. Experiment 2: Protected-protein soybean meal with xylose from Black Liquor’s (BL) of 0, 3, 6, or 9% and extruded at 120, 150, or 180oC, were incubated in ruminal fluid. Experiment 3: The best treatments of experiments 1 and 2 were used as SPN. Sixteen dairy cattle bulls aged 12-15 months were divided into 4 blocks to receive one of the following treatments: R0= rice straw and bran, R1= R0 with SPN A, R2= R0 with SPN B, R3= R0 with SPN C. SPN A, B and C composed of CASREA:SOYXYL in ratio of 20:80, 50:50, and 80:20, respectively. Casrea 2 had the highest microbial protein and post rumen protein digestibility of 29.04 mg and 76.16%, respectively. Protected-protein soybean meal with xylose from BL 3% and extruded at 1500C had the highest microbial protein and post rumen protein digestibility. SPN increased dry matter, organic matter and protein intake and their digestibility, ration efficiency, and daily gain. The highest daily gain (0.85 kg.d-1), ration efficiency (11%), and income over feed cost (Rp 7500 head-1.d-1) were R3. R3 had lower methane energy compare to R0. The result indicated that JDP supplemented with SPN (80% CASREA and 20% SOYXYL) improved ration efficiency and performance of cattle. Key words: rice straw, rice bran, cassava, urea, soybean meal